Effects of residual Si on the ablation properties of biomorphic C/SiC composites for reusable thermal protection systems. (2nd January 2021) - Kim, Joonhui; Kim, Seulgi; Song, Sung Ho; Lee, Dongju
Abstract : Biomorphic C/SiC composites were prepared by infiltrating liquid Si into a carbon preform made from medium-density fiberboard. The effects of residual Si on the ablation properties of the composites were investigated using an oxy-kerosene hypersonic torch. The results revealed that reducing the amount of residual Si plays an important role in increasing the ablation and thermal shock resistances. High residual Si resulted in thermal-shock cracking due to the high thermal expansion coefficient and volume change during melting. The composite infiltrated with 30 wt.% Si showed 0.9 × 10 –4  g/cm 2 ∙s of the ablation rate and no thermal-shock cracking after three successive ablation tests due to the formation of a thin SiO2 layer. Our findings suggest that biomorphic C/SiC composites with minimal residual Si may be suitable as reusable thermal protectors for reentry vehicles.